The Relationship between Job Stress and Employee Performance in Manufacturing Industry in Indonesia - Deasy Lastya Sari; Ribka Intan Putri Sinaga; Helen Storyna; Fergyanto E. Gunawan; Muhammad Asrol; A.A.N. Perwira Redi (Universitas Islam Balitar, 2021)
One-fourth of Indonesia's Gross Domestic Product or GDP is from the manufacturing industry sector. Indonesia's government has proactively encouraged companies to increase their production capacity to meet the global demands, leading to strong demand for employees to work harder, affecting the workers' health. Overwork is often associated with fatigue, stress, and various health problems. Moreover, stress due to excessive work is a general problem many industries face and frequently influences workers' performance. Therefore, this research intends to examine the relationship between work stress and workers' performance, particularly in the manufacturing industry in Indonesia. The sample data are collected from ninety-three workers at the staff level across various companies in the manufacturing sector. The relationships between the determining factors and the Employee Productivity are evaluated by using the multivariate regression analysis. At the correlation coefficient of 0.972, we found a statistically strong relationship between the work environment and Stress to the workers' performance. The condition of low performance is attributed to the non-standard working hours and low quality of the relationship between colleagues and their superiors. Finally, the research recommends improved management of workers' stress by companies involving the adoption of flexible working hours and better communication between parties via discussion forums and meetings. Therefore, employees will be more motivated to improve work productivity.